1999
DOI: 10.1897/1551-5028(1999)018<2875:aicitt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation-Induced Changes in the Toxicity of Zinc and Cadmium to Rainbow Trout

Abstract: Abstract-Adults and juvenile rainbow trout exposed for 21 d to sublethal levels of zinc or cadmium exhibited significant changes in their respective incipient lethal levels (ILL). Acclimation resulted in exposure-dependent changes in both tolerance (ILL concentration) and resistance (time to ILL) in both size classes of fish for each metal. The ILLs for adult rainbow trout exposed to zinc increased from 695 g/L at 131 h for nonacclimated fish to 2,025 /L at 168 h for fish previously exposed to 0.5 ILL (324 g/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…No further increase in copper tolerance was observed in daphnids acclimated to 150 g Cu L Ϫ1 , compared to that of daphnids acclimated to 100 g Cu L Ϫ1 . Similar results of the existence of a certain acclimation plateau also are observed in acclimation experiments with zinc for D. magna [13] and rainbow trout [34]. It may be hypothesized that the increased copper tolerance is leveling off when daphnids are acclimated to a concentration higher than half of the EC50 concentration.…”
Section: Discussionsupporting
confidence: 73%
“…No further increase in copper tolerance was observed in daphnids acclimated to 150 g Cu L Ϫ1 , compared to that of daphnids acclimated to 100 g Cu L Ϫ1 . Similar results of the existence of a certain acclimation plateau also are observed in acclimation experiments with zinc for D. magna [13] and rainbow trout [34]. It may be hypothesized that the increased copper tolerance is leveling off when daphnids are acclimated to a concentration higher than half of the EC50 concentration.…”
Section: Discussionsupporting
confidence: 73%
“…The concept therefore includes an assessment of metal bioavailability as well as an assessment of organism acclimation, both of which have been demonstrated to be important for risk assessments in aquatic environments [22,28]. Using the previously discussed relationships, a series of regional PNEC values was derived using both effects of pH on Zn supply and effects of background Zn on organism response.…”
Section: Application To a Metalloregion Approachmentioning
confidence: 99%
“…The toxicity of Zn salts was not consistently reduced with increasing soil pH. For example, it is well recognized that adaptation or acclimation of aquatic species to varying metal concentrations markedly affects the critical toxicity concentration [21,22]. Similarly, inhibition of respiration by metal salts was compared among five soils and the inhibition by Zn salts was least pronounced in the most acid soil (pH 6.2), whereas the respiration in the soil with highest [20].…”
Section: Introductionmentioning
confidence: 99%
“…Symbols shows average and error bars show ranges across replicates inducing acclimation responses. Stubblefield et al (1999) found that a threshold for pre-exposures of around 0.2× of the Cd or Zn 96-h LC50 concentration appears to be necessary to appreciably increase the resistance of juvenile rainbow trout to Cd or Zn (estimated from their time course to mortality plots; 96-h LC50s were not reported). Pre-exposures to very low Zn concentrations of about 0.05× the LC50 actually sensitized the fish to subsequent Zn exposures.…”
Section: Resultsmentioning
confidence: 99%